Use of technology in undergraduate pharmacy education in selected universities in southern Nigeria - Irenitemi, Enitan O.; Ola-Olorun, Omoniyi J.; Usifoh, Stella F.; Jegede, Ayodapo O.; Eze, Uchenna H.; Fajemirokun, Timothy O. (Tropical journal of pharmaceutical research, 2025)
Purpose: To explore the technologies used in pharmacy education for teaching by lecturers and learning by students in selected universities in Southern Nigeria. Methods: The study involved pharmacy lecturers and undergraduate students from four universities (two federal, one state, one private), selected through purposive and convenience sampling, respectively, using separate questionnaires for lecturers and students. Descriptive analysis, such as frequencies, percentages, and averages, was employed to organize and summarize the data. In contrast, inferential data analysis, including independent samples t-tests, ANOVA and Mann-Whitney U tests, was used to answer questions about differences between relevant variables at 5 % level of significance. Results: Lecturers primarily used computers (83.3 %, avg = 3.7), multimedia projectors (72.7 %, avg = 3.2), Email (74.2 %, avg = 3.2), and WhatsApp (83.3 %, avg = 3.6) for teaching. Students mostly used WhatsApp (96.5 %, avg = 4.5), Wikipedia (86.6 %, avg = 3.9), and YouTube (91.9%, avg = 4.0) for learning. However, the overall adoption of educational technologies, especially Learning Management Systems, was low (avg = 2.6). Conclusion: Technology adoption for teaching and learning in pharmacy education remains low. There is a need for faculty management and educational authorities to establish clear policies to promote effective integration of technology, thereby improving pharmacy education.